2021
DOI: 10.1186/s12879-021-06417-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel scoring model for mortality risk prediction in HIV-infected patients with cryptococcal meningitis

Abstract: Background Cryptococcal meningitis (CM) remains a leading cause of death in HIV-infected patients, despite advances in CM diagnostic and therapeutic strategies. This study was performed with the aim to develop and validate a novel scoring model to predict mortality risk in HIV-infected patients with CM (HIV/CM). Methods Data on HIV/CM inpatients were obtained from a Multicenter Cohort study in China. Independent risk factors associated with mortali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…A superior approach is to combine these two diagnostic methods. We found that seizure and altered consciousness are associated with an increased risk of 1-year death in CM, which is consistent with previous findings (19,20). Moreover, we observed that the number of symptoms shows positive correlation with the risk of death.…”
Section: Discussionsupporting
confidence: 92%
“…A superior approach is to combine these two diagnostic methods. We found that seizure and altered consciousness are associated with an increased risk of 1-year death in CM, which is consistent with previous findings (19,20). Moreover, we observed that the number of symptoms shows positive correlation with the risk of death.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in eight cases of input studies from ML algorithms regarding the ability to predict meningitis disease (including cases related to the discovery of risk factors and identification of high‐risk patients, 46,47,57–59 the risk of death in patients, 50 consequences of disease in childhood, 53 and etiology, 51 in this context, Zhao and colleagues reported that the use of a predictive model can assist clinicians in determining whether lumbar puncture and antibiotic use are appropriate in preterm infants with high‐risk factors. This, in turn, lowers the incidence of unwarranted treatments and sequelae and decreases the chance of missed meningitis diagnoses 50 . In a different study, scientists presented and simulated a model that predicts meningococcal meningitis and its varieties using an AI technique known as the Bayesian Belief Network.…”
Section: Discussionmentioning
confidence: 99%
“…The ML algorithms used in the studies include logistic regression (LR) (25%), 46,48,51,54 multiple logistic regression (MLR) (25%), 50,52,53,61 support vector machine (SVM) (19%), 48,54,56 artificial neural network (ANN) (19%), 47,54,60 random forest (RF) (19%), 52,54,56 decision tree (DT) (12%), 57,58 nave-Bayes (NB) (12%), 52,54 fast-and-frugal trees (FFTs) algorithm (6%), 56 and unsupervised ML approach (6%). 59 The target meningitis diseases in the studies included bacterial meningitis (BM) (37%) [51][52][53]56,57,61 or enteroviral meningitis (EVM) (6%), 56 tuberculous meningitis (TBM) (25%), 48,54,55,61 viral meningitis (VM) (19%), 52,54,55 Neisseria meningitides (6%), 59 lumbar drainagerelated meningitis (LDRM) (6%), 47 healthcare-associated ventriculitis and meningitis (HAVM) (6%), 58 cryptococcal meningitis (CM) (6%), 50 PM (6%), 46 and pediatric purulent meningitis (PPM) (6%). 49…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of standard metrics for SES to enable interstudy comparisons is a major challenge. However, achieving this goal will certainly contribute to improving our understanding of how SES operates and creating successful strategies and interventions for reducing health inequalities ( Zhang et al, 2019 , Zhao et al, 2021 ). Combining data consisting of employment status, education level, national health insurance class, and hospitalization class into a single metric might create a single acceptable global SES measurement.…”
Section: Discussionmentioning
confidence: 99%